2014
DOI: 10.1002/j.2161-1882.2014.00058.x
|View full text |Cite
|
Sign up to set email alerts
|

The Expression of Depressive Symptomatology in Korean American Undergraduates: Sex and Generational Differences

Abstract: This study examined the influence of acculturation and perception of the university environment on the depressive symptomatology of 228 Korean American undergraduates, with a focus on sex and generational differences. Perceptions of the university environment and perceived barriers were positive predictors of depressive symptomatology in respective regression equations by sex and generation. Study limitations and counseling practice implications are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Unexpectedly, differences by gender were not evidenced for the culture-specific approach and in particular enculturation. Given the strong gender-informed roles based on customs and expectations of Indians (Chandra et al, 2016), it is unclear as to why differences did not emerge and are in contrast to Castellanos et al’s (2014) study where Korean American female undergraduates reported higher perception of barriers, both withdraw and stay, than their male counterparts. Although a different Asian ethnic group, it is possible that being in context of higher education equally challenges or even takes precedent to the cultural process of gender-informed norms and expectations for Indian Americans given their high educational focus (Mehra, 2003).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Unexpectedly, differences by gender were not evidenced for the culture-specific approach and in particular enculturation. Given the strong gender-informed roles based on customs and expectations of Indians (Chandra et al, 2016), it is unclear as to why differences did not emerge and are in contrast to Castellanos et al’s (2014) study where Korean American female undergraduates reported higher perception of barriers, both withdraw and stay, than their male counterparts. Although a different Asian ethnic group, it is possible that being in context of higher education equally challenges or even takes precedent to the cultural process of gender-informed norms and expectations for Indian Americans given their high educational focus (Mehra, 2003).…”
Section: Discussionmentioning
confidence: 89%
“…Items are based on a 5-point Likert-type scale ranging from 1 ( Strongly Disagree ) to 5 ( Strongly Agree ). Sample questions include “If I withdrew from college it would be because of not fitting in” and “If I stay in college, I will probably experience negative family attitudes.” Used to examine the expression of depressive symptomatology for 228 Korean American undergraduates, both withdraw (α = .75) and stay (α = .81) had adequate internal consistency (Castellanos et al 2014).…”
Section: Methodsmentioning
confidence: 99%
“…As literature for Korean American undergraduates by groupings is in nascent stage by gender and college generation, our findings are generally aligned with extant findings. Specifically, gender findings emerged for Korean American undergraduate where men reported lower congruity and help-seeking (Gloria et al, 2008) and university environment was a central and more negative predictor for depressive symptomatology (Castellanos et al, 2014) than their women peers. Yet this study’s findings revealed similar patterns with other Asian American ethnic-specific undergraduate research such that differences by groupings emerged by college generation and student standing (Guan, Gloria, et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Increased scores indicate higher perception of barriers prompting withdrawal (e.g., "If I withdrew from college, it would be because of not fitting in"). Castellanos et al (2014) reported adequate subscale Cronbach's α of .75 (withdraw) for Korean American undergraduates.…”
Section: Barriersmentioning
confidence: 99%
See 1 more Smart Citation